The effect of different doses of zinc supplementation on nail elements in elite female athletes - Eskici, G. (Baltic Journal of Health and Physical Activity, 2021)
Background: The trace elements concentration in metabolically inactive fingernails has been used to monitor the exposure to toxic metals or to assess associations between excess or deficiency of trace elements. Material and methods: The research protocol was applied to a total number of 20 female volleyball players. The subjects who were randomly allocated into two groups with an equal number of members were administered 220 mg/day (Group 1) and 440 mg/day (Group 2) of zinc sulfat. Results: The result of the analysis of nail samples collected after 2, 3 and 4 weeks of supplementation showed no significant difference between Mg, Ca, Fe, Cu, Se, P and Zn levels between the groups (p > 0.05). It was determined that nail Ca, Fe, and Zn levels in the last week of zinc supplementation increased significantly compared to the level at the beginning of the supplementation in both groups (p < 0.05). Conclusions: It was determined that two different applications significantly decreased Mg, P and Se levels for both groups regardless of the dose difference.